The Rare Association of Cleft Lip and/or Palate and Wilms Tumor. (September 2019) - Theng, Elizabeth; Tracy, Meghan; Hughes, Susan Starling; Kaye, Alison
There is currently no recognized connection between the occurrence of cleft lip and/or palate (CL/P) and Wilms tumor (WT). A retrospective review of cleft team records (2001-2015) revealed 3 cases of children, all male, with concomitant diagnoses of CL/P and WT treated at our institution. These patients presented as infants for care of their CL/P, all with additional congenital anomalies, developmental delays, and growth delays. Between the ages of 1 and 4 years, each was diagnosed with WT, which was treated with chemotherapy and partial nephrectomy, +/− radiation, leading to full remission in all cases.